Prognosticating post-bariatric surgery outcomes and management of postoperative recurrent weight gain and diabetes recurrence - Xiao, He; Du, Yudie; Tan, Yuanyuan; Ren, Yixing (Frontiers in Nutrition, 2024)
Bariatric surgery stands as the most potent treatment for achieving substantial weight reduction and alleviating the complications associated with obesity. However, it is not the treatment of choice for patients with obesity combined with type 2 diabetes mellitus, and the benefit of bariatric surgery varies widely among individuals. There is a noticeable inconsistency in the outcomes following these procedures. The ability to predict how an individual will respond to bariatric surgery is a valuable asset in clinical practice. And the importance of postoperative interventions should not be underestimated. Proactive measures targeting both pre- and post-operative eating habits and lifestyle adjustments are of greater significance than the investigation into pre-operative factors alone. The judicious application of medication, endoscopic intervention and conversional surgeries after bariatric surgery can yield superior outcomes in managing recurrent weight regain and the recurrence of diabetes, albeit with consideration for the associated complication rates.